Geochemistry of the Turonian-Coniacian strata: New insight into paleoenvironmental conditions of the Tethys, Eastern Pontides, NE Türkiye - Özyurt, Merve; Kandemir, Raif; Yıldızoğlu, Selim (Journal of Asian Earth Sciences: X, 2023)
•The Turonian-Coniacian strata can be considered a transgressive series.•The depositional environment was a continental slope with suboxic conditions.•Our paleoclimate indices indicate warm and humid conditions.•The initiation of drowning can be attributed to the consequences of OAE 2. The eastern part of the Sakarya Zone, known as the Eastern Pontides, is represented by a south-facing carbonate platform during the Late Jurassic-Early Cretaceous. The shallow marine carbonate sedimentation is masked by hemipelagic sedimentation during the Turonian to Coniacian. The Turonian-Coniacian strata are widely exposed in the Gümüşhane area. In this study, we present new microfacies and geochemical data that can provide new insights into the palaeo-oceanic conditions during the time of their deposition. These strata consist of yellow to gray, thick-bedded, graded calcarenites, calcilutite, pelagic limestone, and monogenic conglomerates. The dominant components are carbonate fragments, including dolomites and limestone, as well as allochthonous bioclasts. Volcanic rock fragments, quartz, cherts, and glauconites are also present, with their abundance varying along the section. The micritic component and planktonic fauna exhibit an increasing abundance in the upward direction, indicating a gradual deepening of the depositional environment. Hence, the analyzed samples can be interpreted as transgressive series deposited on slopes or the deep shelf basin. Furthermore, these strata exhibit distinct V/(V+Ni) and Ni/Co ratios without a notable negative Ce anomaly, suggesting relatively oxygen-reduced conditions. They also show a slight enrichment in alkali elements (Rb and Cs) and post-transition elements (Ga), and LREE, indicating intense weathering. The Ga/Rb and K/Al values further support warm and humid Cretaceous conditions. Thus, the Turonian-Coniacian strata offer valuable information about ancient environments, climate conditions, and the basin evolution of the Tethys Ocean in the Eastern Black Sea region.